Analysis Of Internal And External Islamic Education Towards Education Globalization - Nuryakhman, Nuryakhman (English Language, Linguistics, Literature, And Education Journal, 2021)
Islamic education is all activities carried out by a person or an institution to instil teachings and develop Islamic values. By the developments and demands of the times, Islamic education must present itself as flexible, responsive, future-oriented, balanced, oriented to superior quality, egalitarian, fair, democratic, dynamic, open, lifelong. Etc. Islamic education should experience innovation by its nature and character from time to time, starting from the system and institutions. Moreover, today's current global turbulence for Islamic education is a lifestyle, food style, entertainment style, and dress style (food, fun, and fashion). If Islamic education does nothing in the face of advanced and modern technology development, Muslims will certainly be passive spectators, not players.